Varenicline Augmentation in Depressed Smokers: An 8-week, Open-Label Study - Philip, Noah S. (J Clin Psychiatry, 2009)
OBJECTIVE: To assess possible antidepressant effects of varenicline augmentation in outpatients with treatment-resistant depressive disorders and nicotine dependence. BACKGROUND: Varenicline (Chantix) is a nicotinic acetylcholine receptor α4β2 partial agonist and α7 full agonist approved for smoking cessation. Studies of similar compounds have suggested evidence of antidepressant effects. METHODS: Eighteen patients were recruited from a general psychiatric outpatient clinic. Inclusion criteria were 1) primary Axis I depressive disorder, 2) persistent depressive symptoms despite adequate treatment, and 3) current cigarette smoking with nicotine dependence. Patients received varenicline in addition to stable doses of their regular psychotropic medications. Depression symptoms, side effects, clinical global impressions, anhedonia, daily cigarette consumption, and vitals signs were assessed every 2 weeks for 8 weeks. Baseline and endpoint ratings were compared, and the relationship between mood improvement and smoking cessation was examined. The primary outcome variable was mean improvement in depressive symptoms. RESULTS: Fourteen patients (78%) completed the study; 4 discontinued due to side effects, including gastrointestinal (n = 3) and worsened mood/irritability (n = 1). Patients demonstrated significant improvement in depression at endpoint (p < .001), with significant improvement as early as week 2. Eight (44%) patients met criteria for categorical response, and six (33%) reached remission criteria; the overall effect size was large. All patients were interested in smoking cessation, eight (44%) achieved abstinence, and nine (50%) had some reduction in smoking. Improvement in depressive symptoms was correlated with smoking cessation. There was no evidence of treatment-emergent suicidality. CONCLUSION: Open-label varenicline augmentation was associated with significant improvement in mood in a small sample of outpatient smokers with persistent depressive symptoms. Larger, double-blind studies are needed to investigate potential antidepressant effects of varenicline augmentation.